Developing an integrated internet presence : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Technology at Massey University - Lusk, Simon John (Massey University, 1996)
This thesis aims to demonstrate a replicable process for creating an integrated internet presence. An integrated internet presence includes the use of the World Wide Web, Email, Email Lists and Newsgroups. Using the web alone is not using the medium either appropriately or to its full advantage. It has a business orientation, due to the fact that no non profit sites have been developed. Several concepts are dealt with in detail, including: What is the Internet? An Integrated Internet Presence Promoting Web Sites A Promotions or Selling Medium? Appropriate Use of the Medium Competitive Advantage A series of case studies designed to support these concepts form the second half of the thesis. The case studies are predominantly based on existing web sites developed by the author in the past year and a half. Those cases not based on developed sites have been chosen as they illustrate several concepts addressed. Due to the speed that technology is moving, a snapshot in time has been taken. The actual date of the chosen point in time, June 1996, is not as important as the sophistication of the browser. For the purposes of this thesis, the most widespread browser in use at the time of writing, Netscape Navigator 2.0 Netscape 2.0 may be found in Appendix 2, and run either from the CDRom or from the machine of the person viewing the CDRom, is the browser used.
Keywords: Internet; Internet advertising; Internet marketing; Case studies